2013
DOI: 10.22459/ag.20.02.2013.02
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Invention: The Patent Malfunction of Australian Patent Law

Abstract: Despite advice to parliament that patents are granted only for 'a significant advance over what was known and what was available to the public' 2 the evidence shows this is not the standard used. The actual standard is a scintilla-a marginal difference from what is known. The consequence of such a low standard is that thousands of patents are granted for things that contribute no public benefit. Such trivial patents can impede genuinely inventive companies. *** 'The production of the knowledge of how to do in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It is often assumed that patents are only granted for genuine inventions. Evidence from the field of business method patents suggests a very much lower standard (Moir ). The data presented here confirm that patents are granted for inventions with a negligible quantum of inventiveness.…”
Section: Setting the Scenementioning
confidence: 99%
See 1 more Smart Citation
“…It is often assumed that patents are only granted for genuine inventions. Evidence from the field of business method patents suggests a very much lower standard (Moir ). The data presented here confirm that patents are granted for inventions with a negligible quantum of inventiveness.…”
Section: Setting the Scenementioning
confidence: 99%
“…Both cases also illustrate a second type of evergreening patent that is also effective in delaying generic entry. The patent system regularly grants patents for combinations of known substances (Moir ), such as combining a known compound with a known release mechanism (for example, immediate, delayed or extended). With venlafaxine, such a combination patent acted to delay generic competition by 2.5 years.…”
Section: The Case Studiesmentioning
confidence: 99%
“…Evergreening patents are secondary patents held by the owner of the original patent. Evergreening presents a particular problem in countries with low patentability standards, such as Australia and the US 8 , 9 …”
Section: Secondary Patents and Evergreeningmentioning
confidence: 99%
“…Evergreening presents a particular problem in countries with low patentability standards, such as Australia and the US. 8,9 US researchers examined patents granted for two HIV drugs (ritonavir and lopinavir/ritonavir) and found that Abbott owned 82 secondary patents and had a further 26 pending applications in the US, all of which involved small variations on the original patents for these drugs. 9 They found that these evergreening patents could delay generic competition for 19 years beyond the date from which generic entry would have been anticipated.…”
Section: Secondary Patents and Evergreeningmentioning
confidence: 99%
“…33 In Australia the right to amend a patent claim was introduced in 1953 and this policy change has never been evaluated. My study of the doctrines leading to the grant of patents for "inventions" which contribute no new knowledge indicates that many of these would never be granted if the right of amendment were limited (Moir 2013b). Where there is an error that might prejudice grant to an otherwise inventive application, a single right to amendment could be allowed in special circumstances.…”
Section: 5a Incentives To Maintain Patent Standardsmentioning
confidence: 99%